Study of Flavonoid in Apium graveolens L. as a Kirsten Rat Sarcoma Protein Inhibitor in Colorectal Cancer Based on In Silico Study - Abdullah, Abdullah; Putri, Nenis Try Melani; Rosyadah, Nuraini; Ramadhani, Putri; Putri, Siti Aqila Kharisma; Widyananda, Muhammad Hermawan; Kurniawan, Nia; Fatchiyah, Fatchiyah (Universitas Brawijaya, 2023)
Colorectal cancer (CRC) is considered the second deadliest cancer, mainly caused by the mutation of Kirsten Rat Sarcoma (KRAS) type G12D; it’s still undruggable. Flavonoids are secondary metabolites in celery, consisting of apigenin, luteolin, quercetin, and kaempferol. This study aims to analyse the most potential flavonoid compounds in Apium graveolens L. as KRAS inhibitors in CRC with in-silico. This study starts by collecting the 3D structure, Compound ID, formula, and canonical SMILES of compounds from PubChem and the 3D structure of KRAS G12D from the RCSB-PDB. Ligand and protein preparations using OpenBabel PyRx and Biovia Discovery Studio 2019. The SwissADME web server is used to analyse drug-likeness, the PassOnline web server is used to analyse biological activity, docked using PyRx VinaWizard, and visualisation by Biovia Discovery Studio 2019. RMSD and RMSF values were obtained by analysing binding stability with the YASARA application. The molecular docking test showed that chrysoeriol, luteolin, and apigenin have the highest binding affinity and advance to molecular dynamic test. Results of the molecular dynamic showed that chrysoeriol could potentially inhibit the KRAS protein drug in CRC since it also had the lowest toxicity and the strongest binding affinity to the KRAS.